Fatigue predicts quality of life after leucine-rich glioma-inactivated 1-antibody encephalitis - Binks, SNM; Veldsman, M; Handel, AE; Jacob, S; Maddison, P; Coebergh, J; Michael, S; Ramanathan, S; Easton, A; Nissen, MS; Leite, MI; Okai, D; et al. (Wiley, 2024)
Patient-reported quality-of-life (QoL) and carer impacts are not reported after leucine-rich glioma-inactivated 1-antibody encephalitis (LGI1-Ab-E). From 60 patients, 85% (51 out of 60) showed one abnormal score across QoL assessments and 11 multimodal validated questionnaires. Compared to the premorbid state, QoL significantly deteriorated (p < 0.001) and, at a median of 41 months, fatigue was its most important predictor (p = 0.025). In total, 51% (26 out of 51) of carers reported significant burden. An abbreviated five-item battery explained most variance in QoL. Wide-ranging impacts post-LGI1-Ab-E include decreased QoL and high caregiver strain. We identify a rapid method to capture QoL in routine clinic or clinical trial settings.